Basic Understanding of Temporomandibular Joint and Its Dysfunction among Undergraduate Students—A Survey Report - Dandekeri, Shilpa; Kavassery, pooja B.; Hegde, Chethan; Kumar, Sowmya M.; Shetty, Bharathraj (Journal of Health and Allied Sciences NU, 2019)
Background Temporomandibular disorder is the most commonly occurring type of orofacial pain. A general dental practitioner must be able to recognize and distinguish pain related to the joint to be capable of providing treatment or send for a referral. This survey was undertaken to test the undergraduate students in their residency program to analyze their skills in basic understanding and diagnostic capability relevant to temporomandibular joint (TMJ) disorder.Materials and Methods A total of 110 dental students undergoing their residency program in the institute of A.B. Shetty Memorial Institute of Dental Sciences were selected. They were given a questionnaire pro forma to fill out which included questions regarding the anatomy, physiology, pathology, diagnosis, and treatment plan of TMJ disorders.Results Note that 71.75% ± 6.13% of students answered anatomy questions correctly, 46.6% ± 28% answered physiology questions correctly, 34.67% ± 5.5% answered pathology questions correctly, 23.67% ± 2.5% answered diagnosis questions correctly, and 27.25% ± 15.8% answered questions of treatment plan correctly. Note that 100% of them understood the importance of TMJ in dentistry.Conclusion This shows that there is an awareness about the basic understanding of the TMJ; however, to be able to clinically apply the knowledge and diagnose a disorder of TMJ, more than half of the participants were unacquainted of it and the curriculum should stress on improvement of this understanding at the undergraduate level itself.
Keywords: temporomandibular joint; temporomandibular disorder; orofacial pain